2020
DOI: 10.2147/cmar.s275624
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and Safety of Anlotinib for Elderly Patients with Previously Treated Extensive-Stage SCLC and the Prognostic Significance of Common Adverse Reactions</p>

Abstract: Background This study was to investigate the efficacy and safety of anlotinib for elderly patients with previously treated extensive-stage small cell lung cancer (ES-SCLC) and the prognostic significance of common adverse reactions. Patients and Methods A total of 79 elderly patients (≥60 years) with ES-SCLC who failed after at least two lines of previous systemic therapy were included. Baseline characteristics of the patients were collected. Follow-up was conducted reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 43 publications
10
30
0
Order By: Relevance
“…Interestingly, the prognostic significance of adverse reactions in our study suggested that hypertension and HFS induced by regorafenib could be used as potential biomarkers to predict the prognosis of regorafenib treatment, which is in line with ae previous study of the association between HFS and regorafenib efficacy in the treatment of mCRC. 14 Similarly, a recent study using exploratory analysis to investigate the influence of HFS or hypertension on the efficacy of another antiangiogenic small-molecule TKI, anlotinib, for elderly patients with small-cell lung cancer 32 demonstrated that hypertension and HFS might confer superior PFS to no hypertension and HFS, consistent with the clinical significance of hypertension and HFS in our study. To our knowledge, hypertension and HFS are the most common adverse reactions associated with antiangiogenic inhibitors affecting on the VEGF pathway, including bevacizumab, sorafenib, and sunitinib.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the prognostic significance of adverse reactions in our study suggested that hypertension and HFS induced by regorafenib could be used as potential biomarkers to predict the prognosis of regorafenib treatment, which is in line with ae previous study of the association between HFS and regorafenib efficacy in the treatment of mCRC. 14 Similarly, a recent study using exploratory analysis to investigate the influence of HFS or hypertension on the efficacy of another antiangiogenic small-molecule TKI, anlotinib, for elderly patients with small-cell lung cancer 32 demonstrated that hypertension and HFS might confer superior PFS to no hypertension and HFS, consistent with the clinical significance of hypertension and HFS in our study. To our knowledge, hypertension and HFS are the most common adverse reactions associated with antiangiogenic inhibitors affecting on the VEGF pathway, including bevacizumab, sorafenib, and sunitinib.…”
Section: Discussionsupporting
confidence: 88%
“…The incidence of adverse events recorded in both groups was low and similar to those reported in the literature [25,[40][41][42][43][44][45][46]. In this study, the proportion of patients rechecking ECG, thyroid function and urine routine was small.…”
Section: Discussionsupporting
confidence: 86%
“…26 Regarding the elderly patients with lung cancer who received anlotinib therapy, a previous study initiated by PF Song and colleagues included a total of 79 elderly patients with extensivestage small cell lung cancer aged 60 years old or above who were treated with 12 mg anlotinib monotherapy. 15 The results suggested that the preliminary efficacy and safety of anlotinib for elderly patients with previously treated ES-SCLC was satisfactory, which exhibited that patients with lung cancer could stand a good chance to benefit from anlotinib monotherapy. Overall response of anlotinib in elderly patients with advanced NSCLC exhibited that ORR and DCR were 7.2% and 78.3%, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…The results of each imaging assessment were recorded and analyzed to document the best overall response of the patients. 15 Subsequently, follow-up was implemented using phone monthly, and the death status of the patients was mainly obtained through the communication with the relatives of the patients. The last follow-up date of the present study was July, 2021.…”
Section: Methodsmentioning
confidence: 99%